U-Pb mineral ages from northern Labrador: Possible evidence for interlayering of Early and Middle Archean tectonic slices - Schiøtte, L.; Noble, S.; Bridgewater, D. (Geoscience Canada, 1990)
Summary Previous work has shown that a major part ofthe Early Archean (>3500 Ma) rocks in Labrador north of Nain were reworked undergranulite-facies conditions between 2800and 2700 Ma. New U-Pb zircon data show that Middle Archean gneisses are more abundant than previously recognized. Their metamorphic histories differ from the historyof the Early Archean rocks. Part of the Middle Archean gneiss suite was emplaced direct lyin granulite faciès between 3250 and 3200Ma and was partly retrogressed at the time of granitoid veining ca. 2990 Ma. Only after ce.2700 Ma do Early and Middle Archean gneisses have similar histories. We suggest that the terrane model proposed for SW Greenland can be applied to Labrador and that terrane intercalation took place ca. 2700Ma. The Middle Archean gneisses north of Nain are likely to be tectonic slivers equivalent to the Maggo gneiss of the Hopedale area to the south. Correlation between the Middle Archean terrane of Labrador and the Akia terrane in SW Greenland is suggested.